A multitier YinYang-N-element cellular architecture for the Chinese meridian system. (8th January 2010) - Zhang, Wen-Ran; Chen, Su-Shing; Zang, Hongzhao
A multitier YinYang-N-Element cellular architecture is proposed for the Chinese meridian system as a platform for elaboration. Based on this platform, the theoretical and experimental aspects of the Chinese meridian system are discussed. It is argued that when scientists emphasise the importance of "experimental verification of any theory" they must not forget that, after thousands of years of medical practice, acupuncture in particular and TCM in general still do not possess a unique formal logical foundation. It is, therefore, concluded that YinYang and TCM researchers are obligated to make an effort to use some 'pure thought' to grab the reality in mathematical terms instead of only trying to 'distill' the principles from 'experience' or, alternatively, only trying to fit TCM into western medicine.